Net ecosystem production during secondary ecological succession: lessons from the tropical dry forest - Rojas Robles, Nidia E.; Yépez, Enrico A.; Alvarez-Yépiz, Juan Carlos; Sanchez-Mejía, Zulia M.; Garatuza-Payan, Jaime; Rivera-Díaz, Miguel A. (Instituto de Ecología, A.C., 2023)
Ecosystems continuously exchange carbon and water vapor with the atmosphere through ecosystem processes. Net ecosystem production shows the balance between carbon uptake by productivity and carbon release by ecosystem respiration. Evaluating this production along with the changes during secondary ecological succession represents a great challenge. In this context, the eddy covariance technique is widely applied to quantify ecosystem fluxes on a continuous basis. In the case of tropical dry forests, several monitoring sites have been established to investigate the ecosystem functionality during succession using the eddy covariance technique. This information provides insights for decision-makers, in terms of conservation and ecosystem services management, and for scientists to parameterize models to predict the response of these seasonal dry ecosystems to climate change. Tropical dry ecosystems are of great relevance in the carbon cycle due to their large extension and productivity. The challenge of studying these ecosystems lies in understanding the coupling between carbon production and seasonal water availability. The objective of this work is to give an update of those studies related to biosphere-atmosphere interactions using the eddy covariance technique, specifically in tropical dry forests highlighting the effect of ecological succession on carbon dynamics. It also shows and highlights the local-to-global importance of this type of system of functional monitoring of ecosystems across Mexico.